Greater change in bone turnover markers for efavirenz/emtricitabine/tenofovir disoproxil fumarate versus dolutegravir + abacavir/lamivudine in antiretroviral therapy-naive adults over 144 weeks. (28th November 2015) - Tebas, Pablo; Kumar, Princy; Hicks, Charles; Granier, Catherine; Wynne, Brian; Min, Sherene; Pappa, Keith
Abstract : Objective: Antiretroviral therapy initiation has been linked to bone mineral density and bone biomarker changes. We assessed long-term bone turnover biomarker effects over 144 weeks in patients initiating dolutegravir (DTG) + abacavir/lamivudine (ABC/3TC) versus efavirenz/emtricitabine/tenofovir disoproxil fumarate (EFV/FTC/TDF). Methods: Patients randomized in SINGLE received DTG (50 mg once daily) + ABC/3TC or fixed-dose combination EFV/FTC/TDF. We evaluated vitamin D serum levels and bone turnover markers (BTMs), including type 1 collagen cross-linked C-telopeptide (CTx), osteocalcin, bone-specific alkaline phosphatase (BSAP), and procollagen type 1 N-terminal propeptide (P1NP), at baseline and weeks 48, 96, and 144. Results: Among the 833 enrolled patients (68% white, 85% men), baseline median age was 35 years (range 18–85), median CD4 + was 338 cells/μl, and median BMI was 24 kg/m 2 . Fifty-three percent of patients smoked, and 6% reported baseline vitamin D use, with no meaningful differences between groups. Relative to baseline, CTx, osteocalcin, BSAP, and P1NP increased; vitamin D decreased in both groups at weeks 48, 96, and 144. Changes from baseline typically peaked at weeks 48 or 96 and for the four analytes, excluding vitamin D, with the EFV/FTC/TDF group having significantly greater changes from baseline at all time points. Conclusion: DTG + ABC/3TC in antiretroviral therapy-naive patients resulted in significantly lower increases in BTMs (CTx, osteocalcin, BSAP, P1NP) compared with EFV/FTC/TDF over 144 weeks. The observed changes are consistent with results from other smaller, randomized trials. These differences in BTMs likely correlate with changes in bone mineral density over time.